Results of multicenter observation study on application of international questionnaire GerdQ for diagnostics of gastroesophageal reflux disease - V. O. Kaybysheva; Yu. A. Kucheryavyy; A. S. Trukhmanov; O. A. Storonova; M. Yu. Konkov; I. V. Mayev; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Assessment of sensitivity and specificity of the questionnaire GerdQ for diagnostics of gastroesophageal reflux disease (GERD) in everyday practice of primary healthcare level physician in the Russian Federation.Material and methods. Survey by GerdQ questionnaire included 145 patients with symptoms related to upper parts of the gut, who were recommended due to main disease to undergo esophagogastroduodenoscopy (EGDS) and 24-hour intraesophageal pHmetry prior to enrollment to this investigation. After filling the questionnaire all patients were examined by gastroenterologist to establish preliminary diagnosis (GERD or other disease). During the subsequent 2 wks patients underwent EGDS, 24-hour pH-metry and diagnosis was specified. Upon termination of the study the data received after filling of questionnaire and data of physical investigation by gastroenterologist have been compared to results of instrumental methods of GERD diagnostics. Statistical analysis was carried out by application software packs IBM® SPSS® Statistics. Results. Sensitivity of GerdQ questionnaire was 65,4% (87 of 133 patients), specificity – 91,7% (11 of 12 patients).Conclusion. High sensitivity and specificity of GerdQ questionnaire will help physicians and other experts at primary healthcare level to establish diagnosis of GERD, to choose adequate approach at investigation and treatment of patients with symptoms related to upper parts of the gut.